PENGENDALIAN GERUSAN DI SEKITARABUTMEN JEMBATAN - Lutjito, Sudiyono AD (Universitas Negeri Yogyakarta, 2012)
The purpose of this research is to find out local scouring at abutment, and theeffectiveness of ground-sill in the reduction of the depth, by reducing the basicchannel degradation occurs. This research conducted in hydraulics laboratoryDepartment of Civil and Education planning, Faculty of Engineering, UniversitasNegeri Yogyakarta. Three models of ground-sill distance show that a/Dp =2, groundsillcan effect to reducing depth and length of scouring. The result show that a/Dp =2is optimum distance betwen a/Dp =3 and a/Dp =4 respectively.Keyword: abutmen, ground-sill